PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DALAM PEMBELIAN FURNITURE DI PT SARANA TIRTA ABADI SURABAYA - Denta Cristio Ceasar G.; Menur Kusumaningtyas (PUTRA JAWA PUBLISHER, 2024)
Consumer loyalty is a very important factor for companies to maintain business continuity. Loyal customers are customers who are very satisfied with certain products and services, so they have willingness to buy them again or introduce them to new customers. To retain the old customers, the companies must prioritize an excellent service for them more than acquiring the new customers. Therefore, continuous consumer loyalty by building trust, and creating satisfaction by providing quality service is one of the important assets that the company must maintain. This research aims to determine the influence of service quality simultaneously and partially on consumer loyalty and consumer satisfaction in purchasing furniture at PT. Sarana Tirta Abadi Surabaya. Data collection techniques using questionnaires. The sample was 5 respondents who were consumers of PT. Sarana Tirta Abadi Surabaya using a purposive sampling technique. The analysis technique uses multiple linear regression. The results of hypothesis testing show that consumer satisfaction and service quality have a simultaneous and partial effect on consumer loyalty in purchasing furniture at PT. Sarana Tirta Abadi Surabaya. It would be better if the management of PT. Sarana Tirta Abadi increases the value of trust and service quality so that consumer satisfaction with the company can also increase. Companies need to improve quality service, especially regarding the speed of handling consumer complaints.